, , Es stimmt ja immer zugleich alles und nichts": Zur Theorie des Autors und zum Tod als Gegenstand in Interviews: Müller, Bernhard, Derrida. Issue 1 (2nd January 2016) - Wegmann, Thomas
Abstract : After a brief outline of the literary motif of death, this article deals with different theming of death in interviews with contemporary writers. The starting point is the premise that the interview is a form of paratext that allows special presentations of authorship, including an intricate relationship between fact and fiction and between the presence and absence of the author, which is increased once again when the author's own demise is mentioned. In this context, Roland Barthes's "Death of the Author" is read as an implicit heuristic fiction that built an observing system, in which the end of the author is nothing else than the beginning of his literary afterlife in cultural memory.